Overtraining and chronic fatigue: The unexplained underperformance syndrome (UPS) - Budgett, R. (International SportMed Journal, 2000)
All athletes must train hard in order to improve their performance. Some athletes fail to recover from training, become progressively fatigued, and suffer from prolonged underperformance. They may also suffer from frequent minor infections (particularly respiratory infections). This has been called the over training syndrome, burnout, staleness, or sports fatigue syndrome, but in the absence of any medical cause is more accurately called the Unexplained Underperformance Syndrome (UPS). The condition is normally secondary to the stress of training, but the exact etiology and pathophysiology is not known, and many factors other than overtraining may lead to failure to recover from training or competition. Changes in psychological, hormonal, and immune parameters have been shown in these underperforming athletes, some of which may be useful as markers when used on an individual basis. However, the importance of any of these changes, many of which are seen in athletes without UPS when training very hard, is not fully understood. Athletes normally recover in 6 to 12 weeks with a program of gentle exercise and regeneration strategies.